The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1163/156855507779763667
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of new monomer and polymers of hindered silyl styrene

Abstract: Abstract-In this paper we report the synthesis of a new hindered organosilicon derivative of styrene monomer, homo-polymer and co-polymers. This new monomer was synthesized from reaction of the lithiated derivative of para-methyl styrene with tris(trimethylsilyl)silylchloride in room temperature. Homo-polymerization or co-polymerization was done using a free radical polymerization method using α,α -azobis(isobutyronitrile) (AIBN) as a initiator. Incorporation of this bulky group to polymers showed a high glass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Incorporation of a tertiary substituted group into the polymer can significantly increase T g compared to unmodified polymers without this bulky group because the steric hindrance of the bulky group reduces the mobility of the polymer backbone. , In addition, it was also found that the T g increase for ortho substitution is much greater than the T g increase for para substitution, which may be interpreted to mean that the steric hindrance at the ortho position creates a greater restriction on backbone motion because the ortho position is closer to the backbone. Even though the two substituent groups are at meta positions in PDTMSS or PDtBS, they are very bulky and also quite close to the polymer backbone.…”
Section: Resultsmentioning
confidence: 99%
“…Incorporation of a tertiary substituted group into the polymer can significantly increase T g compared to unmodified polymers without this bulky group because the steric hindrance of the bulky group reduces the mobility of the polymer backbone. , In addition, it was also found that the T g increase for ortho substitution is much greater than the T g increase for para substitution, which may be interpreted to mean that the steric hindrance at the ortho position creates a greater restriction on backbone motion because the ortho position is closer to the backbone. Even though the two substituent groups are at meta positions in PDTMSS or PDtBS, they are very bulky and also quite close to the polymer backbone.…”
Section: Resultsmentioning
confidence: 99%
“…This is the expected result because the C-OBMI-St-AGC-APTES sample is obtained by the crosslinking of OBMI-St-AGC-APTES. In the literature, it was explained that the polymer samples showed higher Tg after silanization [ 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…4-Chloromethylstyrene (CMS), also called 4-vinylbenzylchloride (VBC), is a monomer that can be reacted with a series of reagent to produce polymer with functional groups [14][15][16].…”
Section: Introductionmentioning
confidence: 99%